2018
DOI: 10.1126/scisignal.aau7632
|View full text |Cite
|
Sign up to set email alerts
|

The HDAC3–SMARCA4–miR-27a axis promotes expression of the PAX3:FOXO1 fusion oncogene in rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma of childhood with an unmet clinical need for decades. A single oncogenic fusion gene is associated with treatment resistance and a 40 to 45% decrease in overall survival. We previously showed that expression of this PAX3:FOXO1 fusion oncogene in alveolar RMS (aRMS) mediates tolerance to chemo- and radiotherapy and that the class I–specific histone deacetylase (HDAC) inhibitor entinostat reduces PAX3:FOXO1 protein abundance. Here, we established the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 33 publications
2
75
0
Order By: Relevance
“…11 HDACs, which target lysine residues, are epigenetic determinants that are essential for transcriptional regulation via promoting chromatin condensation. 50,51 Tsung-Hua Hsieh and colleagues reported that acetylating RUNX3 enhanced the binding of the RUNX3/ p300 complex to the miR-125a-5p promoter and that silencing RUNX3 had the same biological effect as decreasing miR-125a-5p in human breast cancer cells. RUNX3 plays an important role in transcriptional regulation and the biological effect of miR-125a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…11 HDACs, which target lysine residues, are epigenetic determinants that are essential for transcriptional regulation via promoting chromatin condensation. 50,51 Tsung-Hua Hsieh and colleagues reported that acetylating RUNX3 enhanced the binding of the RUNX3/ p300 complex to the miR-125a-5p promoter and that silencing RUNX3 had the same biological effect as decreasing miR-125a-5p in human breast cancer cells. RUNX3 plays an important role in transcriptional regulation and the biological effect of miR-125a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Our in vivo results can be compared with those of Abraham et al., who described testing for the entinostat and actinomycin D for a single mouse model of ARMS, and to those of Bharathy et al., who studied entinostat in combination with vincristine for PDX models of ARMS . Abraham et al.…”
Section: Discussionmentioning
confidence: 70%
“…Bharathy et al used entinostat administered daily for 21 days at doses of 4 or 25 mg/kg, producing daily exposure to high entinostat levels in contrast to the exposure profile observed in the clinical setting. 37 The impact of the addition of entinostat to the activity of vincristine for the PDX models tested was modest and did not result in statistically significant differences in tumor volume. We confirm that entinostat can cause the slowing of tumor growth for ARMS models, as In summary, we have evaluated entinostat at a dose and schedule of administration that designed to simulate entinostat exposure in patients, within the limitations imposed by mouse versus human differences in entinostat pharmacokinetics.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations